Áhrifaþættir í afköstum fyrirtækja á Íslandi. Hvað gerir góð fyrirtæki framúrskarandi á ólgumiklum markaði? - Kerul, Alina, 1976- (2013)
Since the middle of the 20th century, many theories on corporate performance have been developed and tested. However, most of analytical papers examine corporate performance determinants with respect to one single selected theory. And, not many of them take into consideration the full set of variables (macro-, micro- and organizational) presenting the complete picture of factors affecting corporate performance. As well, the most of previous work is based on data set for big economies. To my knowledge, it is the first analytical analysis of this type for the Icelandic economy. The aim of this thesis is to examine a variety of factors affecting ROA during expansion period, during recession period and during the period of 2005 – 2011. By the end of this research, I will be able to answer the following question:”What make good companies great in a turbulent economy?” This research is based on a dataset received from the Creditinfo Group hf., which I used in the organizational model; and data from Statistics Iceland, Landsbankinn and CBI, which I used in the economic model. The main result of this research is – corporate performance in Iceland is greatly dependent on macro-economic variables, which are outside of firm´s control. Moreover, “great” corporation in Iceland has a high degree of market power and competitive advantage, and is able to sustain them. As well, it minimizes agency costs, has increasing transaction costs, younger CEO and small Board of Directors. However, it doesn’t matter how great corporation is; it is not able to reduce extremely negative impacts of ISK volatility and growth of private consumption.